Problem-based Learning in Basic Physics - XIII - Mody, A. K .; Pradhan, H. C. (SCHOOL SCIENCE, 2018)
In this article— thirteenth in the series of articles— we present problems which are non-numerical or the ones which require minimum mathematics but can be addressed by bare minimum mathematics or simple logic. Many are the situations which have to be understood in the light of laws of physics. This involves serious discussion of the phenomenon or the process and logical analysis.